Insights into Heterologous Biosynthesis of Arteannuin B and Artemisinin in Physcomitrella patens - Nur Kusaira Khairul Ikram; Arman Beyraghdar Kashkooli; Anantha Peramuna; Alexander R. van der Krol; Harro Bouwmeester; Henrik Toft Simonsen (Molecules, 2019)
Metabolic engineering is an integrated bioengineering approach, which has made considerable progress in producing terpenoids in plants and fermentable hosts. Here, the full biosynthetic pathway of artemisinin, originating from Artemisia annua, was integrated into the moss Physcomitrella patens. Different combinations of the five artemisinin biosynthesis genes were ectopically expressed in P. patens to study biosynthesis pathway activity, but also to ensure survival of successful transformants. Transformation of the first pathway gene, ADS, into P. patens resulted in the accumulation of the expected metabolite, amorpha-4,11-diene, and also accumulation of a second product, arteannuin B. This demonstrates the presence of endogenous promiscuous enzyme activity, possibly cytochrome P450s, in P. patens. Introduction of three pathway genes, ADS-CYP71AV1-ADH1 or ADS-DBR2-ALDH1 both led to the accumulation of artemisinin, hinting at the presence of one or more endogenous enzymes in P. patens that can complement the partial pathways to full pathway activity. Transgenic P. patens lines containing the different gene combinations produce artemisinin in varying amounts. The pathway gene expression in the transgenic moss lines correlates well with the chemical profile of pathway products. Moreover, expression of the pathway genes resulted in lipid body formation in all transgenic moss lines, suggesting that these may have a function in sequestration of heterologous metabolites. This work thus provides novel insights into the metabolic response of P. patens and its complementation potential for A. annua artemisinin pathway genes. Identification of the related endogenous P. patens genes could contribute to a further successful metabolic engineering of artemisinin biosynthesis, as well as bioengineering of other high-value terpenoids in P. patens.